Sexual Satisfaction in a Sample of Italian Women during the COVID-19 Lockdown Period - Matilde Buattini; Luca Daminato; Greta Riboli; Mattia Nese; Gianni Brighetti; Daniel Giunti; Rosita Borlimi (Sexes)
This study explored the relationships among psychological, relational, and sexual factors and their impact on sexual satisfaction among Italian women during the COVID-19 lockdown. Data were collected via an online survey with 3803 participants. The survey assessed mental health, relationship quality, frequency of sexual intercourse, frequency of masturbation, body awareness, and sexual satisfaction. Correlation analyses revealed positive relationships among all the variables and negative relationships with low mental health. A network analysis showed that sexual satisfaction was the most central variable, strongly linked to relationship quality, frequency of sexual intercourse, and body awareness. An exploratory mediation model examined the indirect effects of mental health and frequency of masturbation on sexual satisfaction through the other variables as mediators. The results indicated that mental health negatively influenced sexual satisfaction both directly and indirectly through relationship quality and body awareness, while frequency of masturbation had a positive indirect effect through body awareness. These findings highlight the complex interplay among mental health, body awareness, relational factors, and sexual satisfaction, emphasizing the importance of holistic approaches in enhancing sexual well-being. Future research should focus on longitudinal studies to establish causality and explore interventions that promote positive body awareness and relationship quality.